Governance Reforms of State-Owned Enterprises : Lessons from Four Case Studies (Egypt, Iraq, Morocco, and Tunisia) - World Bank (Washington, DC, 2015)
The state-owned enterprise (SOE) landscape has become increasingly diverse. There used to be some relatively well-defined criteria, but with the growing complexity of state participation in the economy, there is no longer a uniform definition, and especially because the definition of a SOE has always been country-specific. SOE reforms can have major positive impacts not only by reducing fiscal risks by decreasing hidden subsidies, direct transfers, and overstaffing, but also by strengthening competition and developing capital markets. SOE reforms in developing countries began in the 1960s because of the poor performance of many of the SOEs. The reform movement sought to strengthen the internal capacity of SOEs. To enrich the discussion about possible avenues for performance-enhancing SOE reforms, this report presents the main principles of good governance of SOEs with references to the Organization for Economic Co-operation and Development (OECD) guidelines on corporate governance of SOEs (OECD 2005). This document is divided into six parts: (1) an effective legal and regulatory framework for SOEs; (2) the state as an owner; (3) equitable treatment of shareholders; (4) relations with stakeholders; (5) transparency and disclosure; and (6) the responsibilities of the boards of SOEs.